Anthobium frigidum Shavrin 2022, comb.nov. - Shavrin, Alexey V. (Zenodo, 2022)
Anthobium frigidum (J. Sahlberg, 1880) comb.nov. (Figs. 67–68, 82–86) Deliphrum frigidum J. Sahlberg, 1880: 108; Luze 1905: 245 Type material examined: Syntypes: 1 ♂: ‘Sibir arct’, ‘J. Sahlb. | ind. typ’, ‘Sibirie Jénissée’, ‘frigidum | J. Sahlb.’, ‘R.I.Sc.N.N. 17.479 | Deliphrum | Coll. et det. A. Fauvel’, ‘Syntype’, ‘ Anthobium | frigidum (J. Sahlberg, 1880) | Shavrin A.V. det. 2021’ <printed> (Fig. 63; IRSN); 3 ♂♂, 4 ♀♀: ‘Tolstoinos’ <printed>, ‘J. Sahlb. | ind. typ’ <printed>, ‘Coll. et det A. Fauvel | Deliphrum [handwritten] | frigidum J.Sahlb. [handwritten] | R.I.Sc.N.B. 17.479’ <printed>, ‘Syntype’ <printed in red, with black frame>, ‘ Anthobium | frigidum (J. Sahlberg, 1880) | Shavrin A.V. det. 2021’ (IRSN); 3 ♂♂: 2 ♀♀: ‘Tolstoinos 70°10’’ <printed>, ‘Sibir Jeniseie’ <printed>, ‘ frigidum J. Sahlb. ’ <handwritten>, ‘J. Sahlb. ind. typ’ <printed>, ‘2319’ <printed> (SMNH). Additional material examined: RUSSIA: TYUMEN AREA: 1 ♂, 1 ♀: Uvatskiy District, 10 km S Gornoslinkino, near Tobolsk Field Research Station of Severtsov Institute. Mosses and litter in forests with Abies , Picea , Betula , Carex globularis , Calamagrostis sp., Equisetum sylvaticum , Pyrola sp., Maianthemum bifolium , Linnaea borealis , Oxalis acetosella , Solidago sp., Lathyrus sp., Lonicera sp., Hylocomium splendens , Pleurozium schreberi , Dicranum polysetum etc. 13.09.2003. A.B. Ryvkin leg. (ZMM); KHANTY- MANSI AUTONOMOUS REGION: 2 ♂♂, 1 ♀: Surgutskiy District, Yuganskiy Nature Reserve, Vachempeu River (right confluent of Bolshoy Yugan River), 3 km SW of Kamenniy codon. Steep loamy bank of river: Carex spp., grasses, sporadic Filipendula ulmaria , Vicia sp., Veronica ? longifolia etc. 21.08.1999. A.B. Ryvkin leg. (cSh, ZMM); 2 ♂♂, 1 ♀: same data, Malyi Yugan River, 3 km up-stream Vuya-Yany River. In geophilous and epigenous fungi and litter among those in flood-plain birch forest with Maianthemum , young Picea and Abies , Rosa sp. etc. 14.08.1998 (cSh); 1 ♀: same data, basin of Kol-Kochen-Yagun River (confluence of Malyi Yugan River), lake near cordon. Mosses and litter under Pinus sylvestris , P. sibirica and Abies in forest at ridge NW of lake with Vaccinium vitis-idaea , V . myrtillus , Linnaea borealis , Pleurozium schreberi , Hylocomium splendens , Dicranum sp., sparse Ledum palustre etc. 01.10.2001 (cSh); TAIMYR AUTONOMOUS REGION: 4 ♂♂, 6 ♀♀: Karaul. 19- 20.08.1994. L.B. Rybalov leg. (cR, cSh); 4 ♂♂, 8 ♀♀: same data, 15- 21.08.1990 (cSh); 2 ♂♂, 4 ♀♀: same data. 11- 12.08.1994 (cR, cSh, ZMM); 1 ♂, 1 ♀: same data, 19- 20.08.1994 (cSh); 15 ♂♂, 38 ♀♀: same data, soil traps. 15- 22.08.1994 (cR, cSh, ZMM); KRASNOYARSK TERRITORY: 3 ♂♂, 4 ♀♀: Turukhanskiy District, Yenisey River, Mirnoye. 18.08.1978. K. Es`kov leg. (ZMM); 1 ♂: same data. 14- 24.06.1991. L.B. Rybalov leg. (ZMM); 4 ♂♂, 1 ♀: same District, Goroshikha. Soil traps. 25- 31.08.1994. L.B. Rybalov leg. (cSh); 2 ♂♂: same data, 24- 30.08.1994 (cSh); 4 ♂♂, 8 ♀♀: same data, 25- 31.09.1994 (cSh, ZMM); 2 ♂♂, 1 ♀: same District, Yeloguy Nature Refuge, Yeloguy River, 6 km below Tyna River mouth. In litter on swamped shore of forest lake with Filipendula ulmaria , Ribes nigrum , Alnus sp., Betula sp. 27.07.1992. V.B. Semenov leg. (cSh); 2 ♂♂, 2 ♀♀: same data, 15.08.1992. (cSh); 8 ♂♂, 5 ♀♀: same data, in litter at swamped shore of forest lake with Filipendula ulmaria , Ribes nigrum , Alnus sp., Betula sp. 27.07.1992 (cSh, ZMM); 1 ♀: same data. Sweeping on motley grasses near riverbank. 28.07.1992 (cSh); 2 ♂♂, 1 ♀: Yeloguy. Traps. 07- 17.07.1989. L.B. Rybalov leg. (cSh, ZMM); 3 ♂♂: Mirnoye. In mushrooms. 05.08.1978. K. Es`kov leg. (cR); 1 ♂: same data, in mosses. 31.08.1977 (cR); 2 ♂♂: same District, Podkamennaya Tunguska River basin, Rybnaya River (I), about 40 km up-stream of river mouth. 190 m a.s.l., slope with Sphagnum spp., Ledum , Oxycoccus sp., Vaccinium vitisidaea , V . myrtillus , Betula , Pinus sylvestris , P. sibirica , Abies , Picea , etc. 13.09.1990. A.B. Ryvkin leg. (ZMM); 1 ♂: same data, Sukhaya River, mouth of Lebyazhya River. 60 m a.s.l., mosses and litter under Picea , Abies , Betula with Vaccinium myrtillus , V . vitis-idaea , Pleurozium , Hylocomium , Polytrichum commune , Sphagnum ? girgensohnii etc. 29.09.1990 (ZMM); EVENKIA: 3 ♂♂: Baykitskiy District, Podkamennaya Tunguska River, 1 km up-stream Sulomay River. 70 m a.s.l., litter and mosses at slope near stream: Picea , Alnus , Betula , Abies , Salix , Pleurozium , Hylocomium etc. 01.10.1989. A.B. Ryvkin leg. (ZMM); ALTAI: 1 ♂, 1 ♀: Altai Mts., Teletskoye Lake, Altaiskiy National Reserve, Chiri Lake, upper timberline of Picea obovata + Pinus sibiricus taiga, mainly at water. 1700- 1750 m a.s.l. 29.07- 01.08.1997. S. Golovatch & A. Tanasevitch leg. (cSh); TUVA: 2 ♂♂, 2 ♀♀: the pass before Zhoigan, 52°35’10’’N 98°47’57’E. 1929 m a.s.l. 28.06.2016. I.V. Enushchenko leg. (cSh); 3 ♂♂, 8 ♀♀: valley of Arzhan-Khem River, 52°32’35’’N 98°43’28’’E. 2280 m a.s.l. 29.06.2016. I.V. Enushchenko leg. (cSh, MHNG); 2 ♀♀: without exact locality. 1985. N.A. Formozov leg. (ZMM); BURYATIA: 2 ♂♂, 1 ♀: Okinskiy District, valley of Dunda-Gol River, 52°35’40’’N 98°50’33’’E. 1689 m a.s.l. 22, 27.06.2017. I.V. Enushchenko leg. (cSh); 1 ♀: same data, 52°35’637’’N 98°50’628’’E. 1678 m a.s.l. 17.07.2015. (cSh); 2 ♂♂, 2 ♀♀: same District, Topografov Pik, valley of Khaelgin River, right bank of the river, willow thicket (in litter). 20.07.2015. I.V. Enushchenko leg. (cSh); 2 ♀♀: same District, Sherpov path, 52°31’444’’N 98°52’938’’E. 2334 m a.s.l. 18.07.2015. I.V. Enushchenko leg. (cSh); 1 ♂, 2 ♀♀: same District, right bank of Daergyl River, 52°34’18’’N 98°56’18’’E. 28.07.2015. I.V. Enushcnenko leg. (cSh). Redescription. Measurements (n=100): HL: 0.42–0.48; HW: 0.57–0.71; AL: 1.17–1.37; OL: 0.15–0.20; PL: 0.50–0.68; PW: 1.03–1.41; ESL: 1.20–1.51; EW: 1.28–1.96; AW: 1.12–1.46; MTbL (averaged): 0.62; MTrL (averaged): 0.41 (MTrL 1–4: 0.22; MTrL 5: 0.19); AedL: 0.58–0.70; TL: 2.80–4.50. Habitus as in Fig. 82. Head, pronotum and abdomen yellow-brown to reddish-brown; antennomeres 4–11 and maxillary palpomeres brown (sometimes two apical palpomeres paler); mouthparts, antennomeres 1–3, lateral and basal portions of pronotum, elytra, legs and sometimes paratergites and apical tergites of abdomen yellow to yellowbrown. Head with dense, transverse microsculpture on clypeus, with or without very indistinct transverse meshes in middle, and with isodiametric or diagonal microreticulation on infraorbital ridges; neck with distinct isodiametric microsculpture; pronotum with or without indistinct isodiametric microreticulation; scutellum without meshes; abdomen with very dense, transverse microsculpture. Head with irregular, moderately fine punctation, denser in middle, usually without punctures along inner sides of anteocellar foveae; neck with regular, sparse and fine punctation; pronotum with dense punctation, coarser and deeper than that on middle portion of head, finer and sparser in middle and/or mediobasal third; scutellum with or without several very fine punctures; punctation of elytra denser, coarser thant that on pronotum, finer and sparser in middle. Head 1.3–1.4 times as broad as long; anteocellar foveae distinct, deep and long, reaching level of apical margin of eye. Ocelli situated at level or slightly below level of postocular ridges. Antennomere 2 slightly narrower than basal antennomere, 3 about as long as or slightly shorter and narrower than 2, 4 slightly shorter and distinctly broader than 3, 5 slightly shorter than 4, 6–7 slightly longer than 5, 8–10 slightly shorter and broader than 7, apical antennomere 1.6–1.8 times as long as preapical antennomere, from apical third gradually narrowed toward rounded or subacute apex. Pronotum wide and convex, twice as broad as long, slightly narrower than head, widest in about middle, evenly narrowed both anteriad and posteriad; anterior angles widely rounded, usually significantly protruded anteriad. Elytra distinctly broader than long, 1.6 times or more than twice as long as pronotum. Metatarsus 1.5 times as long as metatibia. Male. Apical margins of abdominal tergite VIII slightly and sternite VIII widely sinuate. Aedeagus with very wide basal bulb, gradually narrowed toward truncate or widely rounded apex; parameres distinctly exceeding apex of median lobe, widened apically, with two short apical and two preapical setae; internal sac very long and moderately wide, spirally folded in basal portion, with several large subtriangular teeth in basal portion (Figs. 67, 84–85). Lateral aspect of aedeagus as in Fig. 68. Female. Apical margins of abdominal tergite VIII and sternite VIII truncate or rounded. Comparative notes. Regarding the general shape of the body and the aedeagus, and the presence of large subtriangular teeth in the internal sac of the aedeagus, A . frigidum is similar to A . tectum , from which it is distinguished by coarser and denser punctation and more protruding apical angles of the pronotum, and by broader apical portions of the parameres. Distribution. Anthobium frigidum is a Siberian species distributed from the basin of Ob` River in the west to Yenisey River in the east, and to the mountain ranges in Altai and East Sayan in the south (Fig. 86). Natural history. The specimens were found at elevations of 60 to 2334 m a.s.l.. They were collected by sifting mosses and litter in coniferous or mixed forests with Abies , Picea , Pinus , Betula , etc., sometimes in swamped habitats and in fungi. The beetles were observed during the period from June to October, with the greatest number of specimens captured during late summer and autumn. Remarks. Deliphrum frigidum was originally described based on an unspecified number of syntypes from “… territorio frigido prope vicum Tolstoinos 2-6 / 9 copiose capta”. Luze (1905) recorded it from Altai. Veselova & Ryvkin (1991) recorded several specimens from Mirnoye (Krasnoyarsk Territory, Yenisey River). The species is here recorded from Tyumen Area, Khanti-Mansi and Taimyr autonomous regions, Evenkia, Tuva and Buryatia for the first time. : Published as part of Shavrin, Alexey V., 2022, A revision of Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae Omaliinae: Anthophagini). V. Algidum, morosum and tectum groups, a new species of the fusculum group, and faunistic records, pp. 301-346 in Zootaxa 5104 (3) on pages 327-330, DOI: 10.11646/zootaxa.5104.3.1, http://zenodo.org/record/6332042 : {"references": ["Sahlberg, J. (1880) Bidrag till Nordvestra Sibiriens Insektfauna. Coleoptera. Insamlade under Expeditionerna till obi och Jenessej 1876 och 1877. I. Cicindelidae, Carabidae, Dytiscidae, Hydrophilidae, Gyrinidae, Dryopidae, Georyssidae, Limnichidae, Heteroceridae, Staphylinidae och Micropeplidae. Kongliga Svenska Vetenskaps-Akademiens Handlingar, 17 (4), 1 - 115.", "Luze, G. (1905) Revision der palaarktischen Arten der Staphyliniden-Gattung Lathrimaeum Er. Verhandlungen der Kaiserlich- Koniglichen Zoologisch-Botanischen Gesellschaft in Wien, 55, 53 - 69.", "Veselova, E. M. & Ryvkin, A. B. (1991) K faune i ekologii staphylinid (Coleoptera, Staphylinidae) Priyeniseyskoy taigi [On the fauna and ecology of Staphylinidae (Coleoptera) of the Yenissey taiga]. In: [Biological resources and biocenoses of Yenissey taiga]. Institute of evolutional morphology and ecology, Moscow, pp. 178 - 199. [in Russian]"]}